2014
DOI: 10.1007/s10900-014-9900-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tobacco Use and Exposure to Environmental Tobacco Smoke Among Saudi Medical Students in Riyadh, Saudi Arabia

Abstract: This study was designed to determine the prevalence of active smoking and environmental tobacco smoke (ETS) exposure among medical students in Riyadh, Saudi Arabia, and to examine their attitudes and beliefs towards tobacco control programs. The investigation was a cross-sectional study conducted during the first semester of 2013 at King Saud University School of Medicine located in Riyadh, Saudi Arabia. Invited to participate in this study were 1,789 medical students. A descriptive data analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 15 publications
1
12
0
8
Order By: Relevance
“…The Prevalence of tobacco environment exposure was almost constant with the previous studies in the region [22], however, there was a significant increase in the prevalence of home exposure in this study by more than double to be a future risk for the healthcare student as it might increase the health hazards from passive smoking. One of the unique features in our study was the number of female participants, most of the previous local studies were limited to only the male gender hence the low number of female participants, because of that various association between genders were well established.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…The Prevalence of tobacco environment exposure was almost constant with the previous studies in the region [22], however, there was a significant increase in the prevalence of home exposure in this study by more than double to be a future risk for the healthcare student as it might increase the health hazards from passive smoking. One of the unique features in our study was the number of female participants, most of the previous local studies were limited to only the male gender hence the low number of female participants, because of that various association between genders were well established.…”
Section: Discussionsupporting
confidence: 40%
“…The prevalence of medical student's tobacco consumption was noticed to be rising by 6% if compared to a sturdy in King Saud University campus, four years ago, which revealed a significant rising change [22]. The prevalence of water pipe smoking came to be near the prevalence of cigarette smoking and near double the prevalence of small pipe, as most prefer to smoke water pipe in rest places in peripheries of Riyadh especially in social gatherings with friends.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[5] Another study conducted in King Saud University, Riyadh, Kingdom of Saudi Arabia, revealed the estimated prevalence of current smoking among the study participants as 4.7%. [6] The most important independent predictors of smoking were academic performance. [7]…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have assessed these parameters among health-care workers. 14 This study demonstrated that brief interventions could be very fruitful in preparing ASHA workers for tobacco cessation counseling, but the results should be interpreted with caution owing to the absence of randomization in the study design. Apart from this, the outcome variable selected for the study was improvement in beliefs and practices as reported by ASHA workers themselves.…”
Section: Discussionmentioning
confidence: 80%